Miejsce benchmarkingu w strukturze controllingu przedsiębiorstwa - Kowalak, Robert (Benchmarking in controlling structure, 2008)
The article presents the place of benchmarking in the structure of an enterprise, which is applied controlling. It presents solutions taking into account the size of an enterprise: small, medium, and big. The fundamental assumption of the deliberations was that benchmarking is located in the controlling department.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 207-214